1973
DOI: 10.1111/j.1365-2672.1973.tb04107.x
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity for Methane and Methanol of Mixed Cultures Grown on Methane in Continuous Culture

Abstract: ABSTRACT. Pure cultures of Hyphomicrobium sp. had a high affinity for methanol (Km= 8·33 × 10−6 M) and the maximum respiration rate was c. 5 times higher than that of a mixed culture in which a methane‐utilizing pseudomonad predominated (Km= 2·94 × 10−2 M). From a comparison of the substrate affinities, a culture of the methane‐utilizing organism would be expected to produce levels of methanol high enough to inhibit methane oxidation and the Hyphomicrobium sp. would be able to scavenge this methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…It has been suggested that the increased stability of mixed cultures of methane-utilizing bacteria and heterotrophs is due to the utilization of inhibitory intermediate oxidation products of methane by the heterotrophic bacteria (Pirt, 1972;Wilkinson & Harrison, 1973). In our study methanol and formate were not detected in culture supernatants of the methaneutilizing bacterium Methylococcus sp.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…It has been suggested that the increased stability of mixed cultures of methane-utilizing bacteria and heterotrophs is due to the utilization of inhibitory intermediate oxidation products of methane by the heterotrophic bacteria (Pirt, 1972;Wilkinson & Harrison, 1973). In our study methanol and formate were not detected in culture supernatants of the methaneutilizing bacterium Methylococcus sp.…”
Section: Discussionmentioning
confidence: 53%
“…Samples with low activity were incubated for 2 h. Measurement of& values. The effect of various concentrations of methane and methanol on the respiration rate of samples taken from chemostat cultures were determined using an oxygen electrode cell (Harrison, 1973) and K, values for methane and methanol were calculated.…”
Section: Lipolytic Activity Was Detected Using Oxoid Tributyrin Agar mentioning
confidence: 99%
See 3 more Smart Citations